Odd apocalypse - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2012)
Odd Thomas confronts deadly adversaries in a decaying estate.
Keywords: Thomas, Odd (Fictitious character) -- Fiction; Cooks -- Fiction; Mediums -- Fiction; Family secrets -- Fiction; Psychological fiction; Occult fiction; Horror fiction